Pelatihan Pembuatan Media Pembelajaran Interaktif Canva Untuk Peningkatan Ketrampilan Guru di Era Digital: pelatihan media interaktif canva - Meifinda, Yorenza; Sinta Naviri; Safira Vilola; Heldi Apriansyah (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
The digital era requires teachers to always hone their knowledge and skills in using technology. Canva interactive learning media is a media that uses technology because Canve is onlin e- based. This method of community service is carried out in 3 stages, namely, planning, implementation and evaluation. Based on the results of the training, it was found that 16 respondents who took part in the training all experienced an increase in their knowledge and skills